Comparative and international librarianship - Kawatra, P. S. (New Delhi : Sterling Publishers, 1987)
Contributed articles.
1.Comparative librarianship: a theoretical approach 2.Language problems in comparative and international librarianship 3.National central library of the republic of china 4.National library of Nigeria 5.The British library 6.Indian's national library 7.University libraries in Pakistan 8.Contemporary change in the special library environment 9.Trends in library education in Denmark 10.Recent trends in education for librarianship and information in the united kingdom 11.Academic and professional education in the knowledge system in USA 12.Librarianship research in Mexico 13.The all-union institute for scientific and technical information (VINITI) 14.Information referral system
Includes bibliographies and index.
Undergraduate, Graduate and Researchers.
BA (Hons.), MA (Regular), MA (Evening).
Keywords: Comparative librarianship; International librarianship